Women in early medieval China - Hinsch, Bret (Asian voices, 2019)
"This important study provides the only comprehensive survey of Chinese women during the early medieval period of disunion, which lasted from the fall of the Eastern Han dynasty in 220 AD to the reunification of China by the Sui dynasty in 581 AD, also known as the Six Dynasties"--